2018
DOI: 10.1111/jzo.12574
|View full text |Cite
|
Sign up to set email alerts
|

Friendly foxes: the relationship between steroid hormones and social behaviour in a monogamous African canid

Abstract: Aside from some studies on cooperatively breeding species, we know little about the underlying endocrine mechanisms of social behaviour in the order Carnivora. We investigated the correlations between steroid hormones and social behaviour in a socially monogamous canid, the bat‐eared fox (Otocyon megalotis). We collected faecal and observational data over 15 and 22 months, respectively, from 14 wild bat‐eared foxes in the Kalahari Desert, South Africa. These data were used to describe the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
(74 reference statements)
1
2
0
Order By: Relevance
“…Similar to other species, we found different fGCM levels between females and males, with females exhibiting greater concentrations and higher variability than males [ 24 , 49 , 50 , 51 ]; although one study found little variability between sexes [ 23 ]. Trends across sexes are generally not consistent among carnivores and are likely influenced by food quantity and quality, pregnancy status, and whether the individual is actively breeding.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to other species, we found different fGCM levels between females and males, with females exhibiting greater concentrations and higher variability than males [ 24 , 49 , 50 , 51 ]; although one study found little variability between sexes [ 23 ]. Trends across sexes are generally not consistent among carnivores and are likely influenced by food quantity and quality, pregnancy status, and whether the individual is actively breeding.…”
Section: Discussionsupporting
confidence: 84%
“…Both females and males excrete more GCMs during reproductive seasons than non-reproductive seasons, with differences in GCM levels between females and males occurring in some species. For example, female red foxes ( Vulpes vulpes ) had greater variation in peak GCMs than male foxes [ 22 ], while there were no differences in fecal GCM levels between female and male bat-eared foxes ( Otocyon megalotis ; [ 23 ]). Conversely, an individual’s sex and age influenced GCM levels in Mexican grey wolves ( Canus lupus baileyi ; [ 24 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation